RSV attributable mortality in Portugal between 2014 and 2018 - Rodrigues, Ana Paula (2019)
Background: RSV has been recognized as a serious pathogen in at-risk adult populations (long-term care facilities, immunocompromised). In adults, RSV infection is usually mild, but its effects on morbidity and mortality in adults can be substantial as has been previously reported. Given that RSV has a similar seasonality pattern as influenza it is plausible that RSV circulation had contributed to excess all-cause mortality observed during previous winters in Portugal. This study aimed to estimate RSV attributable all-cause mortality between 2014/15 and 2017/18 seasons in Portugal. Methods: Influenza and RSV data (as Goldstein index) was collected by National Influenza Surveillance System and mortality from Portuguese Mortality Surveillance System. Both systems are under coordination of National Health Institute Doutor Ricardo Jorge. Temperatures were downloaded from the National Oceanic and Atmospheric Administration Online Climate Data Directory. An adaptation of FluMOMO model, developed on EuroMOMO network, was used to estimate RSV attributable mortality on studied seasons using data between W40/2014 and W20/2018. Analysis was performed for total (all ages) and specifically for 0-4 years, 5-14 years, 15-64 years and 65 and more years. Non-disaggregated data on Influenza and RSV were used for all age groups. Results: All-cause excess mortality was observed during 2014/15, 2016/17 and 2017/18 winter seasons in Portugal. RSV explained, in those seasons and on total strata, respectively, 12%, 8% and 9% of the observed mortality above the expected during the referred periods.For all age groups under 65 years old RSV attributed mortality was higher than influenza attributable mortality in almost all seasons, although for the 5-14 years old age-group this attributable mortality was not statistically significant. Above 65 years RSV had impact in all-cause mortality in all studied seasons, although with low magnitude than Influenza. Only in 2015/16 when influenza activity was very low with A(H1) dominance, RSV attributable mortality was higher than Influenza attributable mortality. Conclusions: During autumn and winter seasons RSV infections have impacts in all-cause mortality in Portugal. Those findings should be accounted on mortality surveillance systems during the winter season.